2023
DOI: 10.24875/gmm.m18000168
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid as a marker of clinical severity and comorbidities in plaque psoriasis

Abstract: Introduction: Hyperuricemia is common in patients with psoriasis. Uric acid elevation in psoriasis has been suggested to be strongly associated with cardiovascular morbidity. Objective: To determine the relationship between uric acid levels and clinical severity as measured by the Psoriasis Area Severity Index (PASI), body surface area (BSA) and static Physician's Global Assessment (sPGA) in patients with plaque psoriasis and nail comorbidities and psoriatic arthritis. Method: Determination of serum uric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Analysis of the seven studies (15,17,18,29,33,36,41) included in the second part of the meta-analysis showed that the risk of hyperuricemia was high in psoriasis patients. Two studies that performed a subgroup analysis based on sex (33,36) indicated a significant difference in the prevalence of hyperuricemia between the psoriasis and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of the seven studies (15,17,18,29,33,36,41) included in the second part of the meta-analysis showed that the risk of hyperuricemia was high in psoriasis patients. Two studies that performed a subgroup analysis based on sex (33,36) indicated a significant difference in the prevalence of hyperuricemia between the psoriasis and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no cardiovascular disease was mentioned by any of the included studies. Psoriasis is reportedly an independent risk factor for cardiovascular diseases (29,41). However, the relationship between SUA levels and cardiovascular events in psoriasis is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations